Analisis Strategi Sistem Informasi dengan Aplikasi e-Purchasing Menggunakan Metode Ward and Peppard (Studi Kasus Toko ASHA) - I Wayan Yudik Pradnyana; I Wayan Ady Juliantara; I Nyoman Ariana Guna; I Made Agus Widiana Putra (Universitas Tabanan, 2025)
The implementation of the E-Purchasing system in government procurement of goods and services requires an information system strategy that aligns with business needs. ASHA Store is a business actor that utilizes the E-Purchasing application, but its utilization still tends to be operational and is not supported by a structured strategic information system planning. This study aims to analyze and formulate an information system strategy in utilizing the E-Purchasing application at ASHA Store using the Ward and Peppard method. This study uses a qualitative approach with a case study method. The analysis is carried out through analysis of the business environment, IS/IT environment, SWOT, and the preparation of an application portfolio using the McFarlan Strategic Grid. The results show that the E-Purchasing application is a key operational system that supports the main business processes. Recommended strategies include the preparation of IS/IT strategic planning, improving human resource competencies, and developing internal support systems to support decision-making.